从生态学的视角探讨同性恋群体争取对公共空间上的自由权 = Striving for freedom in public space by gay community from an ecological perspective - 潘奕智 Poon, Yoke Chee (2014)
在以往对于邱妙津作品的研究中，较多论文以爱情的角度突出作者对于同性恋爱中之无奈与悲楚。与其往负面的层面去探讨，本论文则以一个在研究邱妙津相对罕见使用的视角，即生态学（Ecology）来探讨她作品里的女同性恋者之处境。近年来，大自然与性别之间产生了许多的争议。其中争论了同性恋的本质是否属于‘自然’。本论文以同性恋‘污染’自然界的陈述为基础，展现异性恋群体的“人类中心主义”（Anthropocentrism）如何以大自然的空间控制女同性恋者的身体活动。笔者同时也凸显异性恋群体的“人类中心主义”特征如何不断对大自然空间进行改革与控制，揭露对破坏大自然的罪魁祸首。笔者将以邱妙津的两部作品，《鳄鱼手记》与《蒙马特遗书》为研究对象。本论文主要以动物意象与其活动空间带出两大点：第一，通过“人类中心主义”指出社会问题，对症下药；第二，通过女同性恋者与大自然的和谐关系对“人类中心主义”进行反抗。从此为同性恋群体开创充满新希望的道路。问题一旦被人们给认可与了解，“人类中心主义”的社会现象将会得到妥善的处理。人们在享用大自然空间所给予的设施时，异性恋群体将能更积极地鼓励与创建对于同性恋权力的公共意识，提倡‘人人都有权利’的口号。Previously, Qiu Miao Jin’s works were broadly interpreted in the perspective of affection to display the frustration and anguish that homosexual relationship has caused. Instead of emphasizing the negative aspect, this thesis uses an Ecological perspective which is rarely used to explore the Qiu Miao Jin, to discuss the situation of the lesbians in her works. Nature and gender have been closely linked together, regarding it, there is one issue which always results in controversy: Whether homosexuality is nature. This paper seeks to build from this statement by highlighting how heterosexual community uses the nature space to oppress the lesbians by displaying anthropocentrism. And also, focuses on how anthropocentrism of heterosexual community could result in the destruction of the ecological environment. Qiu Miao Jin’s E Yu Shou Ji and Meng Ma Te Yi Shu will be used for illustration. In this paper, animal imageries and their point of existence will be used to bring out two points: Firstly, by pointing out the social problem through anthropocentrism and from there, solve it; Secondly, the harmonious relationship between the nature and the lesbians would be displayed to ‘fight’ against anthropocentrism. From which a new path of hope would be created for the gay community. Once the problem is being recognized and understood by the people, anthropocentrism as a social phenomenon would be handled more appropriately. While human beings are given the rights to enjoy in the space given by the nature, heterosexual community could do more to encourage and create public awareness for gay rights in public space, whereby the slogan 'Everyone has the right' will be advocated.